The Effectiveness of Claymation Movie on Students’ Vocabulary Mastery for Indonesian Vocational High School Students - Hanifah, Annisa; Madjdi, Achmad Hilal; Syafei, Muh (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – Vocabulary is an important aspect of learning English, especially in Indonesia, where English is a foreign language. However, monotonous methods often make students bored and have difficulty communicating. Claymation can be an interesting solution and make understanding easier. This study is important to find out whether Claymation media can really help students master vocabulary better.Method – This study uses quantitative methods with the research design used is a pre-experimental one-group pre-test and post-test design that focuses on one class without a control class and changes in learning outcomes cannot be fully attributed to Claymation, so researchers design valid and reliable instruments and conduct trials before being applied to the treatment class. The sample consisted of 36 tenth-grade Animation 1 students in the treatment class. Findings – The results of this study show significant differences. The mean pre-test of 76.22 to the post-test with a mean of 86.33, showing an increase of 10.11 it’s means that many students got a positive rank, which means that the post-test score is higher than the pre-test score, and students have improved. The results of the Wilcoxon test showed sig. value (2 tailed) 0.001 < 0.05. Thus, Ha is accepted, and Ho is rejected. So, the use of Claymation is proven effective in improving students' vocabulary mastery. Research Implications – This study highlights the effectiveness of using Claymation movie which helps in overcoming students' difficulties in vocabulary mastery. The use of Claymation proves that it can increase students' vocabulary, make the classroom atmosphere feel fun, and increase students' learning motivation. In the future, Claymation can be one of the alternative media and solutions for teachers in teaching English to students.